2014
DOI: 10.1371/journal.pone.0099263
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Sialometabolism Present among Oral Fusobacteria

Abstract: Fusobacterium nucleatum is a ubiquitous member of the human oral flora and is associated with the development of periodontitis and a variety of other types of polymicrobial infections of the mucosa. In the oral cavity, this species is one of the few that is prevalent in both healthy and diseased subgingival plaque. Using microarray analysis, we examined the transcriptional response of F. nucleatum subspecies nucleatum to whole blood in order to identify some of the genetic responses that might occur during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 51 publications
5
23
2
2
Order By: Relevance
“…polymorphum strain ATCC10953 generates higher levels of this molecule than a pathogenic strain of E. coli (the encapsulated K1 strain UTI89) under the conditions tested. Our study contrasts with another recent paper that examined sialic acid metabolism among F. nucleatum subspecies and strains (Yoneda et al 2014). The earlier study concluded that de novo sialic acid biosynthesis is widely conserved among the subspecies of F. nucleatum.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…polymorphum strain ATCC10953 generates higher levels of this molecule than a pathogenic strain of E. coli (the encapsulated K1 strain UTI89) under the conditions tested. Our study contrasts with another recent paper that examined sialic acid metabolism among F. nucleatum subspecies and strains (Yoneda et al 2014). The earlier study concluded that de novo sialic acid biosynthesis is widely conserved among the subspecies of F. nucleatum.…”
Section: Discussioncontrasting
confidence: 99%
“…The importance of sialic acids in the pathophysiology of bloodstream infections caused by GBS and E. coli K1 is well known. Although not well studied, the possibility of sialic acid metabolism in F. nucleatum is beginning to attract more attention in the scientific community (Gangi Setty et al 2014;Yoneda et al 2014). However, despite some promising initial studies, rigorous biochemical and genetic experiments establishing that members of this genus encode active sialic acid biosynthetic enzymes and engage in de novo sialic acid biosynthesis have not yet been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Leptotrichia was significantly different between the two groups at the genus level but Fusobacterium showed no difference. More evidence implicated that Fusobacteria was a specific element of the mucosal surface in catarrhal appendicitis and the presence of it correlated positively with the outbreak of the appendicitis [24,26]. Our study presented the similar result.…”
Section: Profile Of Microbiota Composition On the Genus Levelsupporting
confidence: 85%
“…In order to further validate the role of NanT in biofilm formation, sialoglycoproteins and Fusobacteria were used as exogenous sources of sialic acid. T. forsythia can release sialic acid from these glycoconjugates through the mediation of NanH sialidase as shown previously [17, 18, 25], while several Fusobacteria spp., express sialic acid on their surface as recently been shown [7]. We confirmed this in the F. nucleatum ATCC10953 strain by aniline based staining method (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…This ability to target host sialic acids can play important roles in a wide range of biological functions, including cell-cell interactions, immunomodulation, and pathogen recognition [5, 6]. Sialic acid has also recently been shown to decorate the surface of the human oral opportunistic pathogen Fusobacterium nucleatum [7] to which T. forsythia has been shown to aggregate and form synergistic mixed biofilms [8]. …”
Section: Introductionmentioning
confidence: 99%